Metodología para la realización de inventarios físicos en redes viales secundarias con orientación a la conservación vial Caso de estudio vía LojaCatamayo - Requena Vivanco, Marcos Vladimir (2018)
Abstract:The road inventory plays a fundamental role in the conservation of roads, thanks to which it is possible to identify, quantify and assess the conditions of road infrastructure. This work establishes a methodology to carry out physical inventories in secondary road networks, for this the Loja-Catamayo route was selected as a case study, which is very important in the socioeconomic development of the province and its cantons. For the inventory, the georeferenced survey of the road and its components was carried out through the elaboration of different formats corresponding to drainage structures (culverts), containment structures (walls and guardrails) and geological faults that mostly affect the road. counting vehicular traffic. With the collected information, thematic maps were created in Geographical Information System software and a database was generated indicating their geolocation and the state in which each element is found with its respective analysis to propose road conservation measures that facilitate the work that civil engineers must perform.